Cutting edge: the minor histocompatibility antigen H60 peptide interacts with both H-2Kb and NKG2D. - Cerwenka, A; O'Callaghan, C; Hamerman, J; Yadav, R; Ajayi, W; Roopenian, D; Joyce, S; Lanier, L (2002)
Minor histocompatibility Ags elicit cell-mediated immune responses and graft rejection in individuals receiving MHC-matched tissues. H60 represents a dominant Ag that elicits a strong CTL response in C57BL/6 mice immunized against BALB.B. An 8-aa peptide in the H60 protein is presented by H-2K(b) and this is recognized by the TCR as an alloantigen. The intact H60 glycoprotein is a ligand for the costimulatory NKG2D receptor that is expressed by activated CD8(+) T cells. Thus, H60 may provide both an allogeneic peptide and its own costimulation. We show that mutation of an H-2K(b)-binding anchor residue in the H60 peptide completely abrogates binding of H60 glycoprotein to NKG2D and a synthetic H60 peptide partially blocks the binding of NKG2D to its ligand. Ligands of the human NKG2D receptor are remarkably polymorphic, suggesting that these may also serve as minor histocompatibility Ags.